2007
DOI: 10.1063/1.2767972
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low 6,13-pentacenequinone concentration on pentacene thin film growth

Abstract: Thin films of pentacene ͑P͒ have been vacuum codeposited on SiO 2 with low concentrations of 6,13-pentacenequinone ͑PQ͒ in order to investigate the impact on the pentacene thin film structure. Within a range of 2%-20% PQ concentration no intercalation of the compounds can be observed by means of x-ray diffraction and infrared absorption spectroscopy. The crystalline quality of the P films stays unchanged by the presence of PQ, whereas P bulk phase contributions are being suppressed at PQ concentrations ജ5%, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Interestingly, this value is the same ͑within the error margin͒ as the value found for a pure PEN film of =30 nm ͑e = 0.0018Ϯ 0.0005͒ in a previous study. 16 An analogous analysis was done for the film of = 40 nm and yielded values of ͗L͘ V =87Ϯ 12 nm ͑e = 0.0038Ϯ 0.0008͒ and ͗L͘ V =45Ϯ 1 nm ͑e = 0.0015Ϯ 0.0003͒ on the bare and PEN precovered substrate, respectively.…”
Section: Structural Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this value is the same ͑within the error margin͒ as the value found for a pure PEN film of =30 nm ͑e = 0.0018Ϯ 0.0005͒ in a previous study. 16 An analogous analysis was done for the film of = 40 nm and yielded values of ͗L͘ V =87Ϯ 12 nm ͑e = 0.0038Ϯ 0.0008͒ and ͗L͘ V =45Ϯ 1 nm ͑e = 0.0015Ϯ 0.0003͒ on the bare and PEN precovered substrate, respectively.…”
Section: Structural Investigationsmentioning
confidence: 99%
“…46 The investigation of the microstructure was performed applying a Williamson-Hall analysis ͑WHA͒; 16,47,48 the results are shown in Fig. 4͑b͒.…”
Section: Structural Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that these tall islands are crystalline PnQ. 2,6,7,25 Sample AFM images of thick films, displayed in Fig. 2, show that increasing concentration of PnQ during growth causes an abrupt change for PnQ number fractions larger than 0.008 in the ultimate grain sizes and local structure of the bulk film.…”
mentioning
confidence: 99%
“…Analysis of the distribution of capture zones areas of submonolayer islands as a function of impurity content shows that for large PnQ content the critical nucleus size for forming a Pn island is smaller than for low PnQ content. This result indicates a favorable energy for formation of Pn-PnQ complexes, which in turn suggests that the primary effect of PnQ on Pn mobility may arise from homogeneous distribution of PnQ defects.Pac Numbers: 68.65.-k, 05.10.Gg, 73.63.-b, 68.35.bm, 68.55.-a Published as PRB 77, 205328 (2008) The study of organic materials, particularly the various roles of morphology and impurity doping, remains an active subject for device physics, materials design, and applied statistical mechanics.1-3 Studies of the most promising organic electronic semiconductor, pentacene (Pn), have shown that its transport properties are sensitively dependent on crystalline quality 4, 5 and thin film preparation: for the work here, observations that low concentrations of impurities significantly affect film nucleation and growth, electronic transport, and electronic signal noise are of particular interest [6][7][8][9] . Extensive studies of the initial stages of pentacene film growth 3, 10-15 have shown that it follows the classical picture of nucleation, island growth, aggregation and coalescence that was developed for the growth of inorganic films.…”
mentioning
confidence: 99%